Pelatihan Integrasi HOTS dalam Pengembangan Modul Ajar Kurikulum Merdeka pada Guru Bahasa Arab di Pesantren Darullughah Wadda’wah - Mustahar Ali Wardana (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Community Service activity aims to provide training on developing teaching modules for the Merdeka Curriculum in the Arabic language subject to enhance teachers' Higher Order Thinking Skills (HOTS), considering the numerous challenges faced by educators, particularly in adapting to the new curriculum. The applied methods are as follows: (1) Counseling, using techniques such as lectures, Q&A, and discussions on teaching module development; (2) Training, employing techniques like observing models, guiding, and mentoring teachers as they practice composing Arabic language modules according to their assigned duties; and (3) Demonstration, involving techniques such as presentations, simulations, and reflection on the training activities. The results indicate an increase in teachers' professionalism in designing learning tools and a more mature understanding of the Merdeka Curriculum system, reflected in the successful execution of the counseling and mentoring sessions which yielded ready-to-use draft teaching modules.